Avaliação das condições bióticas e abióticas em um viveiro neotropical impactado - Capitanio, Érica Camargo Oliveira [UNESP] (2015)
Limnological studies in fishpond considering physical, chemical and biological characteristics are of extreme importance for the maintenance of the aquatic organisms because such variable are essential to characterize the environment as a whole, permitting to amplify the understanding of the dynamics of the system and allowing the adoption of an adequate local management, increasing the productivity and quality of the commercial activity. An overlook in the planktonic community is a fundamental tool to complete such characterization because such community is composed by sensitive organism dependents upon the quality of the water. Any alteration in such condition may reflect in changes in the abundance and diversity of present species. The main objective of this study was classify the quality of the water of a fishpond located in the Aquiculture Center of the State University of São Paulo in Jaboticabal, SP - Brazil (21°11'S e 48°18'W) in relation to the planktonic community present in the system and the Trophic Status Index. The results showed a planktonic community typical of eutrophic environment with a dominance of the genera: Thermocyclops, Brachionus, Keratella and Trichocerca (zooplankton) and Anabaena, Aphanocapsa and Microcystis (phytoplankton). The Trophic Status Index corroborated with the results found for the planktonic community, classifying all sampled points in the fishpond as eutrophic (varying from 66 to 70). It is possible to conclude that the enrichment of the water column was promoted by the continuous influx in the fishpond, in which carries a higher load of effluents from nurseries and other fishpound located upstream. Such condition becomes the limnological characteristics favorable for the potentially propagation of toxic species as Microcystis aeroginosa and Pseudanabaena catenata from the Cyanobacteria group, calling the attention for an adequate management of the local, avoiding a booming of such ...